Critical excitation methods in earthquake engineering - Takewaki, Izuru (Knovel Library., 2007)
Since the occurrence of earthquakes and their properties are very uncertain even with the present knowledge, it is too difficult to define reasonable design ground motions especially for important buildings. In the seismic resistant design of building structures, the concept of performance-based design has become a new paradigm guaranteeing the maximum satisfaction of building owners.